Mapping SOGI Inclusion through Curriculum and Practice in a Canadian Teacher Education Program - James, Kedrick (Canadian Journal of Education/Revue canadienne de l’éducation, 2020)
Through a faculty-wide program enhancement campaign implemented in a British Columbia university, we investigated sexual orientation and gender identity (SOGI) awareness and inclusion in a Canadian teacher education program. Comparing data from curriculum mapping of course outlines, close analysis of a departmental cross-section of 49 undergraduate syllabi, exit survey data, and 20 interviews with faculty and staff involved in the program, we observed how sustained conversation at all levels of program delivery is indispensable. Curriculum hours of formal SOGI-specific instruction were limited, yet most teacher candidates self-reported that they felt sufficiently prepared to support non-heteronormative students. Findings indicated that SOGI inclusion relies less on formal curriculum than the responsiveness of educators—under sway of progressive policy changes—to have informal, identity-inclusive conversations and to forge connections to curriculum content. Keywords: teacher education, sexual orientation and gender identity, inclusive education, curriculum policy, classroom discourse